Technical aspects of radiation therapy for anal cancer - Scher, Eli D.; Ahmed, Inaya; Yue, Ning J.; Jabbour, Salma K. (Journal of Gastrointestinal Oncology, 2014)
Historically treated with surgery, current practice recommends anal carcinoma to be treated with a combination of chemotherapy and radiation. This review will examine the anatomy, modes of disease spread and recurrence, and evaluate the existing evidence for treatment options for these tumors. An indepth examination of specific radiation therapy (RT) techniques—such as conventional 3D-conformal RT and intensity-modulated RT—will be discussed along with modern dose constraints. RT field arrangement, patient setup, and recommended gross and clinical target volume (CTV) contours will be considered. Areas in need of further investigation, such as the role in treatment for positron emission tomography (PET) will be explored.